A Novel Plated Hepatocyte Relay Assay (PHRA) for In Vitro Evaluation of Hepatic Metabolic Clearance of Slowly Metabolized Compounds - Peng, Chi-Chi; Doshi, Utkarsh; Prakash, Chandra; P. Li, Albert (Drug Metabolism Letters, 2016)
Objective: Development and validation of a novel assay, the Plated Hepatocyte Relay Assay (PHRA), for the determination of the metabolic fates of slowly metabolized compounds. Method: Cryopreserved human hepatocytes were cultured for 4 h followed by incubation with slowly metabolized compounds for 24 h (initial incubation). On the next day, the incubated media were collected and added to hepatocytes was similarly prepared on the day of incubation (48 h incubation; 1st relay). The procedures were repeated on the next days (72 h (2nd relay), 96 h (3rd relay), and 120 h (4th relay) incubations). Results: A proof-of-concept study with two low clearance compounds, diazepam and tolbutamide, and a validation study with 15 ultra-low clearance compounds (CLnon-renal < 1 mL/min/kg) and low clearance compounds (CLnon-renal 1- 5.1 mL/min/kg) were performed. Linear time-dependent disappearance of the parent compounds was observed for all compounds. Application of published free fraction values in combination with a correction factor with in vitro hepatic clearance results obtained with the PHRA accurately predicted in vivo hepatic clearance. Conclusion: PHRA represents a useful experimental system for the evaluation of the metabolic fates of low clearance compounds in drug development..
Keywords: slowly metabolized compounds